2015
DOI: 10.1038/srep08713
|View full text |Cite
|
Sign up to set email alerts
|

The anti-fibrotic effects of mesenchymal stem cells on irradiated lungs via stimulating endogenous secretion of HGF and PGE2

Abstract: Radiation-induced pulmonary fibrosis is a common disease and has a poor prognosis owing to the progressive breakdown of gas exchange regions in the lung. Recently, a novel strategy of administering mesenchymal stem cells for pulmonary fibrosis has achieved high therapeutic efficacy. In the present study, we attempted to use human adipose tissue-derived mesenchymal stem cells to prevent disease in Sprague-Dawley rats that received semi-thoracic irradiation (15 Gy). To investigate the specific roles of mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 47 publications
3
74
0
Order By: Relevance
“…The beneficial effects of MSC-derived HGF observed in vitro (in terms of wound healing and apoptosis) were recapitulated in vivo with significant increases in HGF detected in lungs of mice receiving early administration of MSCs. Moreover, other studies have demonstrated elevated levels of HGF and decreased apoptosis in the lung following MSC administration, [37,55] supporting these findings.…”
Section: Discussionsupporting
confidence: 78%
“…The beneficial effects of MSC-derived HGF observed in vitro (in terms of wound healing and apoptosis) were recapitulated in vivo with significant increases in HGF detected in lungs of mice receiving early administration of MSCs. Moreover, other studies have demonstrated elevated levels of HGF and decreased apoptosis in the lung following MSC administration, [37,55] supporting these findings.…”
Section: Discussionsupporting
confidence: 78%
“…151 Adipose-derived MSCs have also been used for ameliorating radiation-induced pulmonary fibrosis in Sprague-Dawley rats, whereby hepatocyte growth factor ( HGF ) and PGE2 levels increased and TNF-α and TGF-β1 levels decreased after MSC infusion. 152 Another example is the use of BM-MSCs to treat chronic obstructive pulmonary disease, where the BM-MSCs alleviate airway inflammation and emphysema by promoting the down-regulation of cyclooxygenase-2 (COX-2 ) and COX-2-mediated PGE2 production in alveolar macrophages through p38 and ERK. 153 …”
Section: Future Directions Of Mesenchymal Stem Cell Researchmentioning
confidence: 99%
“…In a study of radiation-induced pulmonary fibrosis in Sprague Dawley rats, Dong et al showed a decrease in pro-fibrotic transforming growth factor-β and tumor necrosis factor-α after systemic MSC instillation (Dong et al 2015). The authors speculate that MSCs also inhibit lung fibrosis through the secretion of hepatocyte growth factor and prostaglandin.…”
Section: Mscs Stimulate Tissue Repairmentioning
confidence: 99%